2017
DOI: 10.1111/gcb.13992
|View full text |Cite
|
Sign up to set email alerts
|

Toward ecologically realistic predictions of species distributions: A cross‐time example from tropical montane cloud forests

Abstract: There is an urgent need for more ecologically realistic models for better predicting the effects of climate change on species' potential geographic distributions. Here we build ecological niche models using MAXENT and test whether selecting predictor variables based on biological knowledge and selecting ecologically realistic response curves can improve cross-time distributional predictions. We also evaluate how the method chosen for extrapolation into nonanalog conditions affects the prediction. We do so by e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
138
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(142 citation statements)
references
References 53 publications
0
138
0
4
Order By: Relevance
“…However, all mechanistic models rely to some degree on parameterization against observational data, so they do not entirely avoid the novelty challenge, and their predictions are not necessarily superior to empirical models (Fordham et al., ; Kearney, Wintle, & Porter, ; Shabani, Kumar, & Ahmadi, ). A third solution is to refine correlative models by selecting predictor variables and ecologically realistic response curves based on biological knowledge (Guevara, Gerstner, Kass, & Anderson, ) and by including abundance or population dynamics not just presence–absence, which may provide richer and better‐constrained estimates of species distributions and their governing processes (Howard, Stephens, Pearce‐Higgins, Gregory, & Willis, ). A final solution is to rely on models such as CLMs or joint species distribution models (Clark, Gelfand, Woodall, & Zhu, ) that better incorporate information about species co‐occurrences and implicitly include the processes that drive these patterns.…”
Section: Discussionmentioning
confidence: 99%
“…However, all mechanistic models rely to some degree on parameterization against observational data, so they do not entirely avoid the novelty challenge, and their predictions are not necessarily superior to empirical models (Fordham et al., ; Kearney, Wintle, & Porter, ; Shabani, Kumar, & Ahmadi, ). A third solution is to refine correlative models by selecting predictor variables and ecologically realistic response curves based on biological knowledge (Guevara, Gerstner, Kass, & Anderson, ) and by including abundance or population dynamics not just presence–absence, which may provide richer and better‐constrained estimates of species distributions and their governing processes (Howard, Stephens, Pearce‐Higgins, Gregory, & Willis, ). A final solution is to rely on models such as CLMs or joint species distribution models (Clark, Gelfand, Woodall, & Zhu, ) that better incorporate information about species co‐occurrences and implicitly include the processes that drive these patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, validating these hypotheses of past potential distributions using several GCMs is complicated. Nevertheless, considering paleoecological knowledge can be very useful to make realistic expectations for these distributional predictions (Davis, McGuire, & Orcutt, ; Gavin et al., ; Guevara, Gerstner, et al., ). Unfortunately, paleoecological evidence has been typically overlooked to validate the outcomes of ENM.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Guevara, Gerstner, et al. () analyzed the LGM potential distribution of a small‐eared shrew, Cryptotis mexicanus , a high mountain species from Mexico, using only the CCSM scenario. They found that C. mexicanus showed expansion into middle to lowlands on the eastern slope of a mountain range during the LGM, which could be reflected in a postglacial demographic expansion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, it “anchored” the curves by constraining the models to fit near‐zero suitability where the climate variables exceeded the thresholds of the species, providing a more pronounced delineation of suitability gradients. Second, the response curves spanned a much wider range of environmental conditions than were found in the accessible background, which has previously been shown to be important for accurate spatial and temporal transfer of SDMs (Guevara, Gerstner, Kass, & Anderson, ). Sampling unsuitable conditions only from within the accessible part of the species range would therefore require a greater amount of model extrapolation than our strategy does.…”
Section: Discussionmentioning
confidence: 99%